2004
DOI: 10.1590/s0100-879x2004001100012
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus gallinarum carrying the vanA gene cluster: first report in Brazil

Abstract: In 2000, Enterococcus faecalis resistant to vancomycin was first reported at a tertiary hospital in Porto Alegre, southern Brazil. The resistance spread to other hospitals and surveillance programs were established by hospital infection committees to prevent the spread of vancomycin-resistant enterococci. In February 2002, an isolate initially identified at the genus level as Enterococcus was obtained by surveillance culture (rectal swab) from a patient admitted to a hospital for treatment of septic arthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In 1997, the prevalence of colonization by these species in another hospital in Brazil was 1.2% (Cereda et al 1997), Canada presented 5% of these species (Toye et al 1997), Lebanon 1.4% (Zouain & Araj 2001), and Kuwait 4.5% (Udo et al 2003). The high prevalence obtained in this study is very important because several studies have reported infection or colonization by E. gallinarum carrying genes that determine high resistance to vancomycin: E. gallinarum vanA in Belgium (Dukta-Malen et al 1994), in Italy (Biavasco et al 2001), in Japan (Takayama et al 2003), and in Brazil (Camargo et al 2004). E. gallinarum vanB in Switzerland (Liassine et al 1998) and Australia (Schooneveldt et al 2000).…”
Section: Discussionmentioning
confidence: 52%
“…In 1997, the prevalence of colonization by these species in another hospital in Brazil was 1.2% (Cereda et al 1997), Canada presented 5% of these species (Toye et al 1997), Lebanon 1.4% (Zouain & Araj 2001), and Kuwait 4.5% (Udo et al 2003). The high prevalence obtained in this study is very important because several studies have reported infection or colonization by E. gallinarum carrying genes that determine high resistance to vancomycin: E. gallinarum vanA in Belgium (Dukta-Malen et al 1994), in Italy (Biavasco et al 2001), in Japan (Takayama et al 2003), and in Brazil (Camargo et al 2004). E. gallinarum vanB in Switzerland (Liassine et al 1998) and Australia (Schooneveldt et al 2000).…”
Section: Discussionmentioning
confidence: 52%
“…The presence of E. gallinarum containing vanA isolates has already been described in Brazil and deserves special attention in future studies 10 . Discrepant results for the molecular screening were observed in half of these samples.…”
Section: Introductionmentioning
confidence: 71%
“…Owing to the clinical relevance of such resistance markers, studies to determine the possibility of interspecies transfer of this set of resistance genes are needed. Previous studies have demonstrated that the vanA gene can be transferable from E. gallinarum to E. faecalis and E. faecium strains by conjugation in vitro [16,30]. Enterococcal gene transfer and pheromone-responsive systems may be associated with acquired glycopeptide resistance, especially with the VanA phenotype [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although still rare, high-level acquired vanA-mediated glycopeptide resistance has been described in E. gallinarum and E. casseliflavus recovered in different geographical areas [12][13][14][15][16][17], and natural acquisition of the vanB gene has been associated with E. gallinarum isolates [17][18][19]. Most of the reports are related to faecal colonisation, whilst a few cases of infection have also been documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation